El institucionalismo - Antonio Montaner (Económica, 1955)
The institutionalism is an orientation of American economics, which, abandoning the pure classical theory and the deductive methods, stays in opposition to the mathematical school of the marginal utility. Its adepts insist on an empirical, exact description of the social and economic institutions, which are regulating the individual behavior. The institutionalists try to explain even the formation of prices and values, by the through knowledge of institutional facts. Their interest is thereby directed mainly towards the conjuncture development, the economic constitution and the distribution of income. Economics is for them nothing more than an instrument to social welfare. The institutionalists could not as yet develop a central method in their analysis. They show a preference for either the descriptive, or the quantitative or the causal genetic analysis, as well as for the social-psychological methods, in order to get an idea of the group reactions, by observing the individual behavior. The institutional approach is a stimulus to an historical economic investigation and a contribution to the development of morphological economics and of a really suggestive theory.